Hollow nitrogen-doped carbon-loaded Zn-Co catalyst, preparation method and application
By loading zinc-cobalt on hollow nitrogen-doped carbon-based micro-nanospheres, a highly dispersed catalyst was prepared, which solved the problem of insufficient stability and catalytic activity of non-precious metal-supported catalysts in the prior art, and achieved efficient catalytic effect in organic synthesis reactions.
Patent Information
- Application Number
- CN202411598850.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The prior art is difficult to design and construct stable non-precious metal-supported catalysts, and exhibit low catalytic activity and environmental pollution problems in organic synthesis reactions.
Hollow nitrogen-doped carbon-based micro-nanospheres were used as support, and a highly dispersed zinc-cobalt-supported hollow nitrogen-doped carbon-based nanosphere catalyst was prepared through surface modification, self-assembly coating, calcination and acid treatment steps.
The catalyst showed excellent use stability and high catalytic activity in the N-alkylation reaction and the reduction reaction of nitroaromatic hydrocarbon compound. The reaction activity was basically unchanged for 8 reuses, and the yield reached 96%.
Smart Images

Figure CN119746902A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a hollow nitrogen-doped carbon-supported Zn-Co catalyst, a preparation method and an application thereof. Background Art
[0002] Supported metal catalysts have been proven to be excellent catalysts in a variety of organic synthesis reactions. However, current research is mostly focused on the loading of precious metals such as Au, Ag, Pd, Ru, and Ir, and there are few reports on non-precious metals such as Fe, Co, Ni, Cu, and Zn.
[0003] Non-precious metals can be used as co-catalysts to enhance the activity of precious metals. However, the coordination between non-precious metals and carriers is weak, and they are easily lost during the reaction, leading to environmental pollution and reduced catalyst activity.
[0004] Metal-organic frameworks (MOFs) materials constructed by combining metal salts with organic ligands can stabilize and confine metals well, but the metals are usually in a high-valent state and often show low catalytic activity during catalytic reactions. Some recent reports have shown that M@CN materials obtained by directly calcining MOFs materials can be used as efficient catalysts for catalytic reactions.
[0005] However, the original three-dimensional structure of MOFs materials will inevitably collapse during the calcination process. The M@CN materials after calcination often appear as block or lamellar structures, and the role of the carrier in the catalyst cannot be well reflected.
[0006] Therefore, it is necessary to design and construct stable non-precious metal-loaded catalysts and develop their applications in organic synthesis reactions. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a hollow nitrogen-doped carbon-supported Zn-Co catalyst, a preparation method and an application thereof, which specifically include the following contents:
[0008] A method for preparing a hollow nitrogen-doped carbon-supported Zn-Co catalyst comprises the following steps:
[0009] (1) mixing the hollow nitrogen-doped carbon-based micro-nanospheres with a polydiallyldimethylammonium chloride solution and a polydiallyldimethylammonium chloride solution respectively to obtain modified hollow nitrogen-doped carbon-based micro-nanospheres;
[0010] (2) mixing the modified hollow nitrogen-doped carbon-based micro-nanospheres, zinc nitrate, cobalt nitrate, 2-methylimidazole solution and methanol to obtain hollow nitrogen-doped carbon-based nanospheres supported by a bimetallic zinc-cobalt organic framework;
[0011] (3) The hollow nitrogen-doped carbon-based nanospheres supported by the bimetallic zinc-cobalt organic framework are calcined to obtain highly dispersed zinc-cobalt-supported hollow nitrogen-doped carbon-based nanosphere catalysts.
[0012] Preferably, the concentrations of the polydiallyldimethylammonium chloride solution and the polydiallyldimethylammonium chloride solution in step (1) are equal, and the concentration is 0.1 to 0.5 mol / L.
[0013] Preferably, in step (2), the weight ratio of the modified hollow nitrogen-doped carbon-based micro-nanospheres, zinc nitrate, cobalt nitrate, and 2-methylimidazole solution is 2-3:0.5-1.5:0.5-1.5:30.
[0014] Preferably, the 2-methylimidazole solution in step (2) is a 1 M 2-methylimidazole methanol solution.
[0015] Preferably, the step (3) further comprises:
[0016] After calcination, the calcined product was cooled to room temperature and refluxed in a 1 M hydrochloric acid solution for 3 to 6 hours.
[0017] Preferably, the calcination conditions in step (3) are: a heating rate of 3 to 6°C / min, a final temperature of 800 to 1200°C, and a constant temperature of 2 to 4 hours.
[0018] Preferably, the present invention also provides a hollow nitrogen-doped carbon-supported Zn-Co catalyst prepared by a method for preparing a hollow nitrogen-doped carbon-supported Zn-Co catalyst.
[0019] Preferably, the present invention also provides an application of a hollow nitrogen-doped carbon-supported Zn-Co catalyst in catalyzing N-alkylation reactions and catalyzing reduction reactions of nitroaromatic compounds.
[0020] Preferably, the specific steps of using the hollow nitrogen-doped carbon-supported Zn-Co catalyst in catalyzing N-alkylation reaction are:
[0021] In an inert atmosphere, aniline, benzyl alcohol, KOH and a hollow nitrogen-doped carbon-supported Zn-Co catalyst are mixed in a mass ratio of 20-40:60-80:1:5 and reacted at 100-150°C.
[0022] Preferably, the specific steps of using the hollow nitrogen-doped carbon-supported Zn-Co catalyst in catalyzing the reduction reaction of nitroaromatic compounds are:
[0023] Nitrobenzene, sodium borohydride, water and hollow nitrogen-doped carbon-supported Zn-Co catalyst are mixed in a mass ratio of 200-300:100-120:200-600:1, and reacted at 25-35°C.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention uses hollow nitrogen-doped carbon-based micro-nanospheres, 2-methylimidazole, zinc nitrate, and cobalt nitrate as raw materials, and adopts four steps of surface modification, self-assembly coating, calcination, and acid treatment to obtain a hollow nitrogen-doped carbon-based micro-nanosphere-loaded ultra-dispersed Zn-Co nanoreactor catalyst. The catalyst has excellent stability in both reactions and can be reused 8 times without changing its reaction activity.
[0026] (2) The hollow nitrogen-doped carbon-based micro-nanospheres of the present invention have two main functions: dispersion, which is used to make the active sites more evenly distributed; and electron transport, where the hollow nitrogen-doped carbon-based micro-nanospheres can serve as carriers for electron transport during the reaction and optimize the electronic structure of the catalyst.
[0027] (3) The present invention uses surfactant polydiallyldimethylammonium chloride solution and sodium polystyrene sulfonate solution to modify the surface of hollow nitrogen-doped carbon-based micro-nanospheres, thereby optimizing the distribution of surface charge of the hollow nitrogen-doped carbon-based micro-nanospheres, increasing the specific surface area and electronegativity, thereby enhancing their adsorption effect on metal ions, which is beneficial to the self-assembly coating and uniform surface coverage of ZIF materials.
[0028] (4) The present invention restricts metallic zinc and cobalt in the organic framework structure of ZIF materials and combines them with hollow nitrogen-doped carbon-based micro-nanospheres, thereby greatly reducing the agglomeration of metals during the calcination process and stabilizing the metal particles. The introduction of metallic zinc promotes the uniform coating process of ZIF and the catalytic reaction process, improves the coordination microenvironment around metallic cobalt, and enhances the catalytic reaction activity. The catalyst prepared by the present invention has a yield of 96% in the N-alkylation reaction of aniline and benzaldehyde in a solvent-free-KOH reaction system at 125°C for 18 hours. In the reduction reaction of nitroaromatic compounds, sodium borohydride is used as the hydrogen source in an ethanol / water system and the reaction is carried out at 30°C for 1 hour. It can be seen that the catalyst prepared by the present invention has good catalytic performance and is worthy of promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of the preparation process of the hollow nitrogen-doped carbon-supported Zn-Co catalyst of the present invention;
[0030] Figure 2 It is the substrate expansion diagram of N-alkylation reaction;
[0031] Figure 3 The SEM images of the growth of ZIF-8 with different loading amounts on the modified HCN surface in Example 4 are shown;
[0032] Figure 4 To test the growth of different ZIF-67 loadings on the modified HCN surface in Example 5;
[0033] Figure 5 a is a SEM image of ZIF-8 loaded by a hollow nitrogen-doped carbon-based micro-nanosphere material without surface modification, and b is a SEM image of ZIF-8 loaded by a hollow nitrogen-doped carbon nano-microsphere material with surface modification;
[0034] Figure 6 a is the infrared image of the surface-modified and unmodified hollow nitrogen-doped carbon-based micro-nanosphere materials, b is the Zeta potential of the surface-modified and unmodified hollow nitrogen-doped carbon-based micro-nanosphere materials;
[0035] Figure 7 XRD spectra of the following materials in Example 1 and Comparative Examples 1-2: (a) ZIF-8@HCN, ZIF-67@HCN, ZnCo-ZIF@HCN, HCN; (b) Co@HCN, Zn@HCN, ZnCo@HCN, S-ZnCo@HCN;
[0036] Figure 8 The infrared spectra of the following materials in Example 1 and Comparative Examples 1 to 2 are as follows: (a) ZIF-8@HCN, ZIF-67@HCN, CoZn-ZIF@HCN, HCN; (b) Co@HCN, Zn@HCN, ZnCo@HCN, S-ZnCo@HCN;
[0037] Fig. 9 SEM images of the following materials in Example 1: (a) CoZn-ZIF@HCN, (b) ZnCo@HCN, (c) S-ZnCo@HCN;
[0038] Fig.10 HR-TEM image of the S-ZnCo@HCN material prepared in Example 1;
[0039] Fig.11 This is the XPS spectrum of the S-ZnCo@HCN material prepared in Example 1. DETAILED DESCRIPTION
[0040] The present invention provides a method for preparing a hollow nitrogen-doped carbon-supported Zn-Co catalyst, comprising the following steps:
[0041] (1) mixing the hollow nitrogen-doped carbon-based micro-nanospheres with a polydiallyldimethylammonium chloride solution and a polydiallyldimethylammonium chloride solution respectively to obtain modified hollow nitrogen-doped carbon-based micro-nanospheres;
[0042] (2) mixing the modified hollow nitrogen-doped carbon-based micro-nanospheres, zinc nitrate, cobalt nitrate, 2-methylimidazole solution and methanol to obtain hollow nitrogen-doped carbon-based nanospheres supported by a bimetallic zinc-cobalt organic framework;
[0043] (3) The hollow nitrogen-doped carbon-based nanospheres supported by the bimetallic zinc-cobalt organic framework are calcined to obtain highly dispersed zinc-cobalt-supported hollow nitrogen-doped carbon-based nanosphere catalysts.
[0044] In the present invention, the specific process of mixing in step (1) is:
[0045] The hollow nitrogen-doped carbon-based micro-nanospheres are ultrasonically dispersed in a polydiallyldimethylammonium chloride solution, filtered, the filter residue is washed with water, and then ultrasonically dispersed in the polydiallyldimethylammonium chloride solution again.
[0046] In the present invention, the concentrations of the polydiallyldimethylammonium chloride solution and the polydiallyldimethylammonium chloride solution in step (1) are equal, and the concentration is preferably 0.1 to 0.5 mol / L, more preferably 0.1 to 0.4 mol / L, and more preferably 0.1 to 0.3 mol / L.
[0047] In the present invention, the weight ratio of the modified hollow nitrogen-doped carbon-based micro-nanospheres, zinc nitrate, cobalt nitrate, and 2-methylimidazole solution in step (2) is preferably 2-3:0.5-1.5:0.5-1.5:30.
[0048] In the present invention, the 2-methylimidazole solution in step (2) is preferably a 1M 2-methylimidazole methanol solution.
[0049] In the present invention, the step (3) further comprises:
[0050] After calcination, the calcined product was cooled to room temperature and refluxed in a 1 M hydrochloric acid solution for 3 to 6 hours.
[0051] In the present invention, the calcination conditions in step (3) are: the heating rate is preferably 3-6°C / min, the final temperature is preferably 800-1200°C, and the temperature is kept constant for 2-4h.
[0052] The present invention also provides a hollow nitrogen-doped carbon-supported Zn-Co catalyst prepared by a preparation method of a hollow nitrogen-doped carbon-supported Zn-Co catalyst.
[0053] The present invention also provides an application of a hollow nitrogen-doped carbon-supported Zn-Co catalyst in catalyzing N-alkylation reactions and catalyzing reduction reactions of nitroaromatic compounds.
[0054] The specific steps of using the hollow nitrogen-doped carbon-supported Zn-Co catalyst provided in the present invention in catalyzing N-alkylation reaction are:
[0055] In an inert atmosphere, aniline, benzyl alcohol, KOH and a hollow nitrogen-doped carbon-supported Zn-Co catalyst are mixed in a mass ratio of 20-40:60-80:1:5, and reacted at 100-150° C.
[0056] The specific steps of using the hollow nitrogen-doped carbon-supported Zn-Co catalyst provided in the present invention in catalyzing the reduction reaction of nitroaromatic compounds are:
[0057] Nitrobenzene, sodium borohydride, water and hollow nitrogen-doped carbon-supported Zn-Co catalyst are mixed in a mass ratio of 200-300:100-120:200-600:1, and reacted at 25-35°C.
[0058] The present invention also provides a method for preparing hollow nitrogen-doped carbon-based micro-nanospheres, the specific steps of which are as follows:
[0059] Mix Triton Tx-100, distilled water, aniline, pyrrole and 1M ammonium persulfate solution in a weight ratio of 1:1000:5-8:4-7:100, stir at 0-5°C until the solution changes to blue-black, let stand for 6-15 hours, filter with a 0.4-0.5 μm microporous filter membrane, wash the filter residue with water and ethanol successively, dry at 40-60°C for more than 6 hours, transfer to an inert atmosphere, increase the temperature to 600-1200°C at a heating rate of 4-6°C / min, calcine at a constant temperature for 2-5 hours, and then cool naturally to room temperature to obtain hollow nitrogen-doped carbon-based micro-nanospheres.
[0060] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0061] Example 1
[0062] This embodiment provides a method for preparing a hollow nitrogen-doped carbon-supported Zn-Co catalyst:
[0063] (1) Preparation of hollow nitrogen-doped carbon-based micro-nanospheres
[0064] 0.30 g of Triton Tx-1000, 300 mL of distilled water, 1.91 mL of aniline, and 1.45 mL of pyrrole were added to a 500 mL beaker, and the compound was completely dispersed in the solution by ultrasonication at 50 Hz for 1 h. The solution was then transferred to a jacketed reaction bottle, and circulating coolant was introduced to maintain the temperature within the range of 0 to 5 ° C. Stirring was continued for 1 h. 30 mL of 1 M ammonium persulfate solution pre-cooled in advance was slowly added to the reaction bottle, and vigorously stirred for 5 min to mix it evenly. When the color of the solution changed from colorless and transparent to blue-black, stirring was stopped, and the solution was placed in a refrigerator at 0 ° C and allowed to stand overnight. The catalyst was filtered through a 0.45 μm microporous filter membrane, and the solution was clarified by washing with water and ethanol. The solid was placed in a vacuum oven at 60 ° C and dried for 8 hours for use. The sample was labeled as: PACP.
[0065] Take 4.00 g of PACP sample, put it in a strip crucible with a lid, and calcine it in a tube furnace under Ar gas atmosphere. The heating program is: heat to 800°C at 5°C / min at room temperature, stay for 3 hours, and then cool naturally to room temperature. The sample is marked as: HCN.
[0066] (2) Surface modification of hollow nitrogen-doped carbon-based micro-nanospheres
[0067] Take 200 mg of HCN material, add 30 mL of 0.2 mol / L PDDA (polydiallyldimethylammonium chloride) solution, ultrasonically disperse and react for 1 hour, filter and separate, wash with water, and record it as PDDA-HCN. Disperse PDDA-HCN in 30 mL of 0.2 mol / L PSS (sodium polystyrene sulfonate) solution again, continue ultrasonic reaction for 1 hour, filter and separate, wash with water, and vacuum dry, and record it as PSS-PDDA-HCN.
[0068] (3) Preparation of hollow nitrogen-doped carbon-based nanospheres supported by bimetallic ZnCo organic framework
[0069] 200 mg of modified HCN material was dispersed in 30 mL of methanol solution and ultrasonically dispersed for 30 minutes. 0.08 g of zinc nitrate and 0.08 g of cobalt nitrate were added and ultrasonicated for another 30 minutes. Then, the material was transferred to a jacketed reaction bottle and precooled to 0°C. 1 M 2-methylimidazole dissolved in 30 mL of methanol was added to the reaction bottle. The reaction was stirred at zero degree for 1.5 hours, and the temperature was raised to 40°C for 30 minutes. The material was centrifuged, washed with methanol, and dried in vacuo. It was recorded as ZnCo-ZIF@HCN.
[0070] (4) Preparation of highly dispersed ZnCo-loaded hollow nitrogen-doped carbon-based nanosphere catalysts
[0071] The ZnCo-ZIF@HCN was placed in a tube furnace under an argon atmosphere and heated to 800°C at a rate of 5°C / min, then calcined at 800°C for 2 hours and naturally cooled to room temperature to obtain a sample recorded as ZnCo@HCN.
[0072] The obtained ZnCo@HCN material was placed in a 1 M hydrochloric acid solution for reflux reaction for 4 hours, and the sample obtained after filtration, washing and drying was recorded as S-ZnCo@HCN.
[0073] Example 2
[0074] This embodiment provides a method for preparing a hollow nitrogen-doped carbon-supported zinc and cobalt catalyst:
[0075] (1) Preparation of hollow nitrogen-doped carbon-based micro-nanospheres
[0076] 0.30 g of Triton Tx-1000, 300 mL of distilled water, 1.63 mL of aniline, and 1.27 mL of pyrrole were added to a 500 mL beaker, and the compound was completely dispersed in the solution by ultrasonication at 50 Hz for 1 h. The solution was then transferred to a jacketed reaction bottle, and circulating coolant was introduced to keep the temperature within the range of 0 to 5 ° C and continued to stir for 1 h. 30 mL of 1M ammonium persulfate solution pre-cooled in advance was slowly added to the reaction bottle, and vigorously stirred for 5 min to mix it evenly. When the color of the solution changed from colorless and transparent to blue-black, stirring was stopped, and it was placed in a refrigerator at 0 ° C and allowed to stand overnight. The catalyst was filtered through a 0.40 μm microporous filter membrane, and the solution was clarified by washing with water and ethanol. The solid was placed in a vacuum oven at 60 ° C and dried for 8 hours. 4.00 g of the solid was taken, placed in a strip crucible with a lid, and calcined in a tubular furnace under an Ar gas atmosphere. The heating program is as follows: heating to 600°C at 4°C / min at room temperature, staying for 5 hours, and then naturally cooling to room temperature to obtain hollow nitrogen-doped carbon-based micro-nanospheres.
[0077] (2) Surface modification of hollow nitrogen-doped carbon-based micro-nanospheres
[0078] Take 200 mg of hollow nitrogen-doped carbon-based micro-nanospheres, add 30 mL of 0.1 mol / L polydiallyldimethylammonium chloride solution, ultrasonically disperse and react for 1 hour, filter and separate, and wash with water; the above-obtained material is dispersed in 30 mL of 0.1 mol / L sodium polystyrene sulfonate solution, continue ultrasonic reaction for 1 hour, filter and separate, wash with water, and vacuum dry to obtain hollow nitrogen-doped carbon-based micro-nanospheres.
[0079] (3) Preparation of hollow nitrogen-doped carbon-based nanospheres supported by bimetallic ZnCo organic framework
[0080] 200 mg of the modified hollow nitrogen-doped carbon-based micro-nanosphere material was dispersed in 30 mL of methanol solution and ultrasonically dispersed for 30 minutes. 0.05 g of zinc nitrate and 0.05 g of cobalt nitrate were added and ultrasonicated for another 30 minutes. Then, the material was transferred to a jacketed reaction bottle and precooled to 0°C. 1 M 2-methylimidazole dissolved in 30 mL of methanol was added to the reaction bottle. The reaction was stirred at zero degree for 1 hour, and the temperature was raised to 30°C for 30 minutes. The material was centrifuged, washed with methanol, and dried in vacuo to obtain hollow nitrogen-doped carbon-based nanospheres loaded with a bimetallic ZnCo organic framework.
[0081] (4) Preparation of highly dispersed ZnCo-loaded hollow nitrogen-doped carbon-based nanosphere catalysts
[0082] The above-mentioned metal-loaded material was placed in a tubular furnace under an argon atmosphere and heated to 600°C at 4°C / min, and then calcined at 600°C for 4 hours. The sample obtained after calcination was refluxed in a 1M hydrochloric acid solution for 3 hours, filtered, and the filter residue was washed with water and dried to obtain a highly dispersed zinc-cobalt loaded hollow nitrogen-doped carbon-based nanosphere catalyst.
[0083] Example 3
[0084] This embodiment provides a method for preparing a hollow nitrogen-doped carbon-supported zinc and cobalt catalyst:
[0085] (1) Preparation of hollow nitrogen-doped carbon-based micro-nanospheres
[0086] 0.30 g of Triton Tx-1000, 300 mL of distilled water, 2.27 mL of aniline, and 1.89 mL of pyrrole were added to a 500 mL beaker, and the compound was completely dispersed in the solution by ultrasonication at 50 Hz for 1 h. The solution was then transferred to a jacketed reaction bottle, and circulating coolant was introduced to keep the temperature within the range of 0 to 5 ° C and continued to stir for 1 h. 30 mL of 1M ammonium persulfate solution pre-cooled in advance was slowly added to the reaction bottle, and vigorously stirred for 5 min to mix it evenly. When the color of the solution changed from colorless and transparent to blue-black, stirring was stopped, and it was placed in a refrigerator at 0 ° C and allowed to stand overnight. The catalyst was filtered through a 0.50 μm microporous filter membrane, and the solution was clarified by washing with water and ethanol. The solid was placed in a vacuum oven at 60 ° C and dried for 8 hours. 4.00 g of the solid was taken, placed in a strip crucible with a lid, and calcined in a tubular furnace under an Ar gas atmosphere. The heating program is as follows: heating to 1000°C at 6°C / min at room temperature, staying for 2 hours, and then naturally cooling to room temperature to obtain hollow nitrogen-doped carbon-based micro-nanospheres.
[0087] (2) Surface modification of hollow nitrogen-doped carbon-based micro-nanospheres
[0088] Take 300 mg of hollow nitrogen-doped carbon-based micro-nanospheres, add 30 mL of 0.5 mol / L polydiallyldimethylammonium chloride solution, ultrasonically disperse and react for 1 hour, filter and separate, and wash with water; the above-obtained material is dispersed in 30 mL of 0.5 mol / L sodium polystyrene sulfonate solution, continue ultrasonic reaction for 1 hour, filter and separate, wash with water, and vacuum dry to obtain hollow nitrogen-doped carbon-based micro-nanospheres.
[0089] (3) Preparation of hollow nitrogen-doped carbon-based nanospheres supported by bimetallic ZnCo organic framework
[0090] 300 mg of the modified hollow nitrogen-doped carbon-based micro-nanosphere material was dispersed in 30 mL of methanol solution and ultrasonically dispersed for 30 minutes. 0.15 g of zinc nitrate and 0.15 g of cobalt nitrate were added and ultrasonicated for another 30 minutes. Then, the material was transferred to a jacketed reaction bottle and precooled to 0°C. 1 M 2-methylimidazole dissolved in 30 mL of methanol was added to the reaction bottle. The reaction was stirred at zero degree for 2 hours, and the temperature was raised to 50°C for 30 minutes. The material was centrifuged, washed with methanol, and dried in vacuo to obtain hollow nitrogen-doped carbon-based nanospheres supported by a bimetallic ZnCo organic framework.
[0091] (4) Preparation of highly dispersed ZnCo-loaded hollow nitrogen-doped carbon-based nanosphere catalysts
[0092] The above-mentioned metal-loaded material was placed in a tubular furnace under an argon atmosphere and heated to 1000°C at 6°C / min, and then calcined at 1000°C for 2 hours. The sample obtained after calcination was refluxed in a 1M hydrochloric acid solution for 6 hours, filtered, and the filter residue was washed with water and dried to obtain a highly dispersed zinc-cobalt loaded hollow nitrogen-doped carbon-based nanosphere catalyst.
[0093] Comparative Example 1
[0094] This embodiment provides a method for preparing a hollow nitrogen-doped carbon-supported Zn catalyst:
[0095] (1) Same as Example 1.
[0096] (2) Take 200 mg of HCN material, add 30 mL of 0.2 mol / L PDDA (polydiallyldimethylammonium chloride) solution, ultrasonically disperse and react for 1 hour, filter and separate, wash with water, and disperse the above-obtained material in 30 mL of 0.2 mol / L PSS (sodium polystyrene sulfonate) solution, continue ultrasonic reaction for 1 hour, filter and separate, wash with water, and vacuum dry for standby use.
[0097] (3) 200 mg of the modified HCN material was dispersed in 30 mL of methanol solution and ultrasonically dispersed for 30 minutes. 0.08 g of zinc nitrate was added and ultrasonicated for another 30 minutes. Then, the mixture was transferred to a jacketed reaction bottle and precooled to 0 °C. 1 M 2-methylimidazole dissolved in 30 mL of methanol was added to the reaction bottle. The mixture was stirred at zero temperature for 1.5 hours, heated to 40 °C for 30 minutes, centrifuged, washed with methanol, and dried in vacuo. The mixture was recorded as ZIF8@HCN.
[0098] (4) ZnCo-ZIF8@HCN was placed in a tube furnace under argon atmosphere and heated to 800°C at a rate of 5°C / min, then calcined at 800°C for 2 h and naturally cooled to room temperature to obtain a sample recorded as Zn@HCN.
[0099] Comparative Example 2
[0100] This embodiment provides a method for preparing a hollow nitrogen-doped carbon-supported Co catalyst:
[0101] (1) Same as Example 1.
[0102] (2) Take 200 mg of HCN material, add 30 mL of 0.2 mol / L PDDA (polydiallyldimethylammonium chloride) solution, ultrasonically disperse and react for 1 hour, filter and separate, wash with water, and disperse the above-obtained material in 30 mL of 0.2 mol / L PSS (sodium polystyrene sulfonate) solution, continue ultrasonic reaction for 1 hour, filter and separate, wash with water, and vacuum dry for standby use.
[0103] (3) 200 mg of the modified HCN material was dispersed in 30 mL of methanol solution and ultrasonically dispersed for 30 minutes. 0.08 g of cobalt nitrate was added and ultrasonicated for another 30 minutes. Then, the mixture was transferred to a jacketed reaction bottle and precooled to 0 °C. 1 M 2-methylimidazole dissolved in 30 mL of methanol was added to the reaction bottle. The mixture was stirred at zero temperature for 1.5 hours, heated to 40 °C for 30 minutes, centrifuged, washed with methanol, and dried in vacuo. The mixture was recorded as ZIF67@HCN.
[0104] (4) ZnCo-ZIF67@HCN was placed in a tube furnace under argon atmosphere and heated to 800°C at a rate of 5°C / min, then calcined at 800°C for 2 h and naturally cooled to room temperature to obtain a sample denoted as Co@HCN.
[0105] Comparative Example 3
[0106] This embodiment provides a method for preparing a hollow nitrogen-doped carbon-supported Zn-Co catalyst:
[0107] (1) Same as Example 1.
[0108] (2) Disperse 200 mg of HCN material in 30 mL of methanol solution and ultrasonically disperse for 30 minutes. Add 0.08 g of zinc nitrate and 0.08 g of cobalt nitrate and ultrasonically disperse for another 30 minutes. Then transfer to a jacketed reaction bottle and precool to 0°C. Add 1 M 2-methylimidazole dissolved in 30 mL of methanol to the reaction bottle. Keep stirring at zero degree for 1.5 hours. Heat to 40°C for 30 minutes. Centrifuge, wash with methanol, and vacuum dry. Recorded as ZnCo-ZIF / HCN-1.
[0109] (3) ZnCo-ZIF@HCN-1 was placed in a tube furnace under argon atmosphere and heated to 800 °C at 5 °C / min, then calcined at 800 °C for 2 h and naturally cooled to room temperature to obtain a sample named ZnCo / HCN-1.
[0110] Comparative Example 4
[0111] This comparative example provides a method for preparing a supported Zn catalyst obtained by calcining ZIF-8 material alone:
[0112] 0.08 g of zinc nitrate was added to a jacketed reaction bottle and precooled to 0°C. 1 M 2-methylimidazole dissolved in 30 mL of methanol was added to the reaction bottle. The reaction was stirred at zero degree for 1.5 hours, and the temperature was raised to 40°C for 30 min. The reaction was centrifuged, washed with methanol, and dried in vacuo. It was recorded as Zn-ZIF@CN.
[0113] The Zn-ZIF@CN was placed in a tubular furnace under an argon atmosphere and heated to 800°C at a rate of 5°C / min, then calcined at 800°C for 2 hours and naturally cooled to room temperature to obtain a sample recorded as Zn@CN.
[0114] Comparative Example 5
[0115] This comparative example provides a method for preparing a supported Co catalyst obtained by calcining ZIF-67 material alone:
[0116] 0.08 g of cobalt nitrate was added to a jacketed reaction bottle and precooled to 0°C. 1 M 2-methylimidazole dissolved in 30 mL of methanol was added to the reaction bottle. The reaction was stirred at zero degree for 1.5 hours, and the temperature was raised to 40°C for 30 min. The reaction was centrifuged, washed with methanol, and dried in vacuum. It was recorded as Co-ZIF@CN.
[0117] Co-ZIF@CN was placed in a tubular furnace under argon atmosphere and heated to 800°C at 5°C / min, then calcined at 800°C for 2 hours and naturally cooled to room temperature. The obtained sample was recorded as Co@CN.
[0118] Application Example 1
[0119] Application in catalytic N-alkylation reactions
[0120] In the embodiment of the present invention, the N-alkylation reaction of aniline and benzyl alcohol was also used to evaluate the activity of the catalyst. The reaction conditions were optimized as shown in Table 1. First, the solvent of the reaction was screened. The solvation effect of the solvent has a great influence on the reaction. O-xylene and toluene have better reaction effects as solvents, and the yield can reach 87% and 79% (entries 1, 2). Water, ethanol, acetonitrile and DMF have poor effects, and the yield is between 14 and 45% (entries 3-6). However, it is exciting that under solvent-free conditions, the reaction effect is very good, the conversion rate of aniline reaches 98%, and the yield of the target compound is 97% (entry 7). Next, the effects of several bases are compared under solvent-free conditions. Under the action of strong base, a higher yield (KOH: 97%, KOMe: 87%) can be obtained, and the yields of potassium phosphate, cesium carbonate, and potassium carbonate are 68%, 67%, and 44%, respectively (entries 9-11). The blank experiment shows that the reaction can also be carried out without the addition of an external base, but the yield is low, only 25% (entry 12). This indicates that the base is not necessary in the reaction process, and the base may play a role in accelerating the reaction process. After that, the temperature and time were optimized (entries 13-16). After comprehensive consideration, the optimal reaction conditions were obtained: potassium hydroxide, 125°C, 3mmol aniline, 6mmol benzyl alcohol, 5mg catalyst, reaction time of 18 hours, aniline conversion rate of 98%, and target compound yield of 96%.
[0121] The catalyst-catalyzed N-alkylation reaction equation is as follows:
[0122]
[0123] Table 1 Catalytic reaction conditions screening table
[0124]
[0125]
[0126] The present invention also uses aniline and benzyl alcohol with different substituent groups to test the universality of the catalyst in the reaction system. The results are as follows: Figure 2 As shown, when there is an electron-donating group at the para position of benzyl alcohol, the reaction activity is improved (3b and 3c). When the para position of benzyl alcohol is substituted by a large sterically hindered benzene ring, the yield is slightly reduced due to the steric effect (3d). The steric effect is obvious in the reaction with 3,5-dimethoxybenzyl alcohol as the substrate, and the yield is reduced to 83% (3e). The activity of the electron-withdrawing substituent group on benzyl alcohol is lower than that of the electron-donating group (3f). In addition to the substituent groups on benzyl alcohol, the activity of 3-methyl, 4-methoxy, and 4-chloro groups on aniline was also tested, and the target compounds (3g-3i) were obtained with medium or higher yields.
[0127] This embodiment provides an application of a hollow nitrogen-doped carbon-supported zinc and cobalt catalyst in catalyzing N-alkylation reactions:
[0128] 3 mmol aniline, 6 mmol benzyl alcohol, 10 mg hollow nitrogen-doped carbon-supported zinc, cobalt catalyst, and 0.9 mmol KOH were added to a 10 mL reaction tube, and the mixture was reacted at 125° C. under argon protection for 18 hours.
[0129] Application Example 2
[0130] Application in catalytic reduction of nitroaromatic compounds
[0131] In addition to the N-alkylation reaction, the embodiments of the present invention also use S-ZnCo@HCN catalyst to test its catalytic activity in the reduction reaction of nitroaromatic compounds in the liquid phase. The reaction conditions are optimized as shown in Table 2. First, sodium borohydride was selected as the reducing agent, and the reaction solvent was screened. Considering the green nature of the reaction, the reaction activity in alcohol solvents and water was tested. The catalyst can obtain the target compound with a yield of 94% in ethanol, and the yield in methanol is slightly higher than that in ethanol (95%). Although the yield in pure water is lower than that in alcohol solvents, the reaction can also be completed with a yield of 87%. Using a mixed solvent of ethanol and water, the yield can be increased to 98%. This may be due to the common advantages of the two solvents in the mixed solvent, which can be beneficial to the dissolution of the reactants and the dispersion of the catalyst at the same time. In addition, the activity of hydrazine hydrate as the reducing agent was tested. Unfortunately, the catalyst cannot catalyze the reaction when hydrazine hydrate is the reducing agent. Finally, the reaction time and catalyst dosage were optimized, and the best reaction conditions were obtained: a mixture of water and ethanol = 1:1 as solvent, sodium borohydride as reducing agent, 3 mg of S-ZnCo@HCN catalyst, 1 hour reaction at 30°C, and the yield can reach 97%. The reaction formula of the reduction reaction of nitroaromatic compounds catalyzed by S-ZnCo@HCN catalyst is as follows:
[0132]
[0133] Table 2 Optimization table of nitro reduction reaction conditions
[0134] Serial number Solvents reducing agent temperature time catalyst Yield 1 Ethanol <![CDATA[NaBH4]]> 30 3 5 94 2 Methanol <![CDATA[NaBH4]]> 30 3 5 95 3 water <![CDATA[NaBH4]]> 30 3 5 87 4 Water: ethanol = 1:1 <![CDATA[NaBH4]]> 30 3 5 98 5 Water: ethanol = 1:1 Hydrazine hydrate 30 3 5 99 6 Water: ethanol = 1:1 <![CDATA[NaBH4]]> 30 1 5 98 7 Water: ethanol = 1:1 <![CDATA[NaBH4]]> 30 0.5 5 73 8 Water: ethanol = 1:1 <![CDATA[NaBH4]]> 30 1 3 97 9 Water: ethanol = 1:1 <![CDATA[NaBH4]]> 30 1 1 69
[0135] This embodiment provides an application of a hollow nitrogen-doped carbon-supported zinc and cobalt catalyst in catalyzing the reduction reaction of nitroaromatic compounds:
[0136] In a 15 mL reaction bottle, 1 mmol of nitrobenzene, 1.5 mmol of sodium borohydride, 5 mg of hollow nitrogen-doped carbon-supported zinc, a cobalt catalyst, and 2 mL of water were added, stirred and mixed evenly, reacted at 30° C., and the reaction progress was monitored by thin layer chromatography.
[0137] Test Example 1
[0138] This test example provides a method for testing the activity of hollow nitrogen-doped carbon-supported zinc and cobalt catalysts in catalytic N-alkylation reactions:
[0139] 3mmol aniline, 6mmol benzyl alcohol, 5mg catalyst, 1.5mmol KOH were added to a 10mL reaction tube, and 7 groups of experiments were set up in parallel. The catalysts were ZnCo@HCN, ZnCo-ZIF@HCN and S-ZnCo@HCN in Example 1, Zn@HCN in Comparative Example 1, Co@HCN in Comparative Example 2, Zn@CN in Comparative Example 4, and Co@CN in Comparative Example 5. Other conditions remained unchanged. The reaction was carried out under argon protection at 125°C for 18 hours. After the reaction was completed, the reaction was quenched, the organic phase was collected, and then the conversion rate and yield were determined by gas chromatography (n-hexadecane as internal standard). Each sample was tested three times and the average value was taken. Chromatographic conditions: column phase initial temperature: 80°C, the heating program was 10°C / min to 180°C, and maintained for 10min. Chromatographic column: Agilent HP-5 capillary column.
[0140] Test Example 2
[0141] This test example provides a method for testing the activity of hollow nitrogen-doped carbon-supported zinc and cobalt catalysts in catalytic nitro reduction reactions:
[0142] Add 1mmol nitrobenzene, 1.5mmol sodium borohydride, 5mg S-ZnCo@HCN, and 2mL water to a 15mL reaction bottle, stir and mix evenly, react at 30°C, and use thin layer chromatography to detect the reaction progress. Other conditions remain unchanged, take different reaction substrates, catalyze nitro reduction reaction, and react for 1 hour.
[0143] Test Example 3
[0144] Catalyst recycling performance test
[0145] (1) Catalytic N-alkylation reaction cycle activity test
[0146] Add 3mmol aniline, 6mmol benzyl alcohol, 5mg S-ZnCo@HCN, and 1.5mmol KOH to a 10mL reaction tube, and react under argon protection at 125℃ for 18 hours. After the reaction is completed, quench the reaction, collect the organic phase, and then determine the yield by gas chromatography (n-hexadecane as internal standard). Each sample is tested three times and the average value is taken. After each reaction is completed, filter and separate the catalyst, wash with ethyl acetate, vacuum dry at 60℃, and then reuse it for the next round of reaction. Repeat this process after each reaction. Chromatographic conditions: column phase initial temperature: 80℃, heating program is 10℃ / min to 180℃, and keep for 10min. Chromatographic column: Agilent HP-5 capillary column.
[0147] (2) Catalytic nitrobenzene reduction reaction cycle activity test
[0148] Add 1mmol nitrobenzene, 1.5mmol sodium borohydride, 5mg S-ZnCo@HCN, and 2mL water to a 15mL reaction bottle, stir and mix evenly, react at 30°C, and use thin layer chromatography to detect the reaction progress. After each reaction is completed, filter and separate the catalyst, wash with ethyl acetate, vacuum dry at 60°C, and then reuse for the next round of reaction. Repeat this process after each reaction is completed.
[0149] Test Example 4
[0150] Detection of the effect of different loading amounts on the growth of ZIF-8 on the modified HCN surface
[0151] While keeping other conditions unchanged, during the experimental preparation process, 200 mg of modified HCN and a sufficient amount of 2-methylimidazole (0.84 g) were added, and the feeding amounts of zinc nitrate were controlled to be: 0.32 g, 0.24 g, 0.16 g, and 0.08 g, respectively.
[0152] Test Example 5
[0153] Detection of the effect of different loading amounts on the growth of ZIF-67 on the modified HCN surface
[0154] Keeping other conditions unchanged, during the experimental preparation process, 200 mg of modified HCN and a sufficient amount of 2-methylimidazole (0.84 g) were added, and the amount of cobalt nitrate added was controlled to be: 0.32 g, 0.24 g, 0.16 g, and 0.08 g respectively.
[0155] Test results
[0156] Table 3 is a comparative table of the catalytic activities of the catalysts prepared in Example 1 and Comparative Examples 1 to 5 in the catalytic N-alkylation reaction activity test.
[0157] Catalyst type Aniline conversion rate / % Yield / % Zn@HCN 31 27 Co@CN 79 76 Zn@HCN 33 31 Co@HCN 85 83 ZnCo@HCN 93 92 S-ZnCo@HCN 98 96 ZnCo / HCN-1 82 80
[0158] It can be seen from Table 3 that the catalytic activity of Zn@CN material obtained by calcining ZIF-8 alone is very low with a yield of only 27%. The conversion rate of aniline obtained by calcining Co@CN material with ZIF-67 is 79% and the yield of the target compound is 76%, which indicates that the activity of Co is stronger than that of Zn in this reaction system. ZIF-8 and ZIF-67 are loaded on HCN to obtain ZIF-8@HCN and ZIF-67@HCN, and then calcined to obtain Zn@HCN and Co@HCN materials, whose activities are higher than those without HCN loading, indicating that HCN as a carrier promotes the catalytic activity. When ZnCo@HCN prepared by calcining ZnCo-ZIF@HCN material loaded with metal cobalt and zinc is used as a catalyst, the reaction activity is significantly improved, and the conversion rate of aniline reaches 93%, which indicates that there is a synergistic effect of bimetallic when Co and zinc exist at the same time. According to the information from XRD, there is a ZnS impurity phase in the ZnCo@HCN catalyst, and it is accompanied by the agglomeration of some metals. The experimental results show that the activity of S-ZnCo@HCN material in the N-alkylation reaction of aniline and benzyl alcohol is significantly higher than that of ZnCo@HCN material. The conversion rate of aniline is 98%, and the yield of the target product is 96%. This shows that the agglomerated metal particles and ZnS substances are not the real catalytic active sites, and the metal dispersed on HCN plays a catalytic role. Finally, the bimetallic catalyst ZnCo / HCN-1 prepared from unmodified HCN was used as a catalyst. The yield of the target compound was only 80%, which was much lower than that of ZnCo@HCN and S-ZnCo@HCN materials. This once again shows the role of the carrier HCN. Although HCN itself cannot catalyze the reaction, it can promote the improvement of catalytic activity as a carrier of metals.
[0159] Table 4 is a table showing the substrate expansion and yield of nitroaromatic compounds in the catalytic nitro reduction reaction activity test
[0160]
[0161]
[0162]
[0163] Table 4 shows the substrate expansion and yield of nitroaromatic compounds in the catalytic nitro reduction reaction activity test. It can be seen from the table that the catalyst has good universality in different substrates and can obtain the target compound with a medium or higher yield. In comparison, the electron-donating group is more active than the electron-withdrawing group. In different substitution positions, the para position has the highest activity, followed by the meta position, and the ortho position has the lowest activity. This may be related to the spatial structure of the substitution group, and the ortho position has a large steric hindrance. Among the halogen elements, F has the highest yield, while Cl and Br have the lowest yield, which is related to electronegativity, but iodine is more active than chlorine and bromine substitutions, which may be due to the particularity of the iodine group atom. In addition, compounds substituted with naphthalene and benzyl bromide also obtain the target compound with excellent yields.
[0164] Table 5 is a table showing the cyclic activity test of the S-ZnCo@HCN catalyst prepared in Example 1 in N-alkylation reaction and nitrobenzene reduction reaction.
[0165]
[0166] Table 5 shows the cyclic experimental performance of the S-ZnCo@HCN catalyst in the N-alkylation reaction and the nitrobenzene reduction reaction. Because the N-alkylation reaction requires a strong base and 125°C, the reaction conditions are more stringent, so the yield of the S-ZnCo@HCN catalyst is slightly reduced during the cyclic use, but the yield of the target compound can still reach 90% in the eighth cycle. In the nitro reduction reaction, the catalyst is used multiple times, and the activity remains basically unchanged, and the experiment can be completed with a yield of more than 92%. In short, the S-ZnCo@HCN catalyst has good recyclability, and the target compound can still be obtained with a medium or higher yield after multiple uses.
[0167] Depend on Figure 3 It can be seen that when the zinc nitrate feed amount is 0.32g, ZIF-8 particles gather in large quantities on the surface of modified HCN. After coating the modified HCN, the remaining material grows in the gaps of the composite material, resulting in serious bonding. The size of the ZIF-8 particles growing in the gaps is significantly larger than the particles coated on the surface of the modified HCN material. With the decrease of the zinc nitrate feed amount, the coating of ZIF-8 on the modified HCN becomes more regular. When the zinc nitrate feed amount is 0.16g and 0.08g, the surface is evenly coated and the spherical structure is clearly visible.
[0168] Depend on Figure 4It can be seen that when ZIF-67 is grown in situ on the surface of modified HCN using cobalt nitrate as a raw material, the coating is not ideal. ZIF-67 will aggregate on the surface of the material, resulting in a part of the modified HCN not being coated, and the particle size of ZIF-67 obtained under this experimental scheme is significantly larger than that of ZIF-8. Regulating the feeding amount of different cobalt nitrates does not improve the problem of uneven loading. This uneven coating will cause a part of the metal organic framework material to exist independently in the material, and cannot well reflect the synergistic effect after combining it with the HCN material.
[0169] like Figure 5 As shown in a, for HCN materials without surface modification, ZIF-8 cannot be directional coated.
[0170] like Figure 5 As shown in Figure b, it can be clearly observed that the surface of the surface-modified HCN material is relatively evenly coated with ZIF-8 particles, which shows that surface modification is the key to achieving uniform coating of ZIF-8.
[0171] like Figure 6 As shown in a, the infrared spectrum of the HCN material modified with PDDA solution is at 1047 cm -1 、883cm -1 Two new peaks appeared at 1617 cm-1, which may be related to the attachment of PDDA molecules on the surface of HCN material. After the modification with PSS solution, the peaks at these two locations weakened, but the original peak at 1617 cm-1 was -1 The peak at 1586 cm-1 was slightly shifted to 1586 cm-1. -1 This may be related to the change of the overall structural charge of the material.
[0172] like Figure 6 As shown in Figure b, the Zeta of the HCN material surface is 18.3mV, and the Zeta of the DDA-HCN material is 33.5mV. This is because PDDA is a cationic surfactant, which optimizes the surface charge of the HCN material. The Zeta of the PSS-PDDA-HCN material modified by anionic surfactant is -22.0mV, and the charge on the HCN surface is modified from positive to negative, which is more conducive to the adsorption and attachment of metals on the surface. Therefore, ZIF-8 can grow evenly along the surface of the modified material.
[0173] like Figure 7 As shown in a, ZIF-8@HCN, ZIF-67@HCN and Co / Zn-ZIF@HCN materials all show the characteristic peaks of metal organic frameworks. Since the three materials are MOFs materials synthesized using 2-methylimidazole as raw material, the characteristic peaks of the three materials are basically the same, which also proves that MOFs and HCN materials are successfully composited.
[0174] Figure 7 b is the spectrum of the calcined material and the S-ZnCo@HCN material obtained by the final acid treatment. After calcining ZIF-8@HCN in an argon atmosphere, the Zn@HCN material shows a group of obvious diffraction peaks, which are confirmed to be the diffraction peaks of ZnS after analysis. After tracing the source of sulfur in the material, it is believed that (NH4)2S2O8 was used as an oxidation initiator in the synthesis of HCN material. Although most of the sulfur has been removed in the process of preparing HCN material by calcining PACP material, there is still a very small amount of sulfur in the material. When ZIF-8@HCN material is calcined to prepare Zn@HCN material, although it is pyrolyzed in an argon atmosphere, since the S element is very easy to combine with the Zn element, the ZnS species are preferentially generated when the ZIF-8 on the composite material is pyrolyzed. Because HCN is an amorphous carbon material, ZnS has a high degree of crystallinity, so it shows obvious diffraction peaks in the spectrum. However, the above phenomenon did not occur when ZIF-67@HCN was calcined to prepare Co@HCN material, and the peaks in the obtained material were confirmed to be peaks of Co metal. This is related to the properties of metal compounds, and sulfur elements do not combine with Co elements. The peaks of two phases of ZnS and Co metal appeared in the ZnCo@HCN material obtained by calcining Co / Zn-ZIF@HCN. Usually, sharp diffraction peaks will appear in the XRD spectrum only when metal compounds agglomerate together to form particles. Therefore, it is considered to place the ZnCo@HCN material in a 1M hydrochloric acid solution for reflux reaction for 4 hours to remove the agglomerated metal and ZnS and other impurities on the surface of the material. It can be found that the diffraction peaks of the final S-ZnCo@HCN material are basically consistent with HCN, showing only the amorphous broad peaks of the carrier skeleton, and the diffraction peaks of the metal disappear, indicating that the remaining metal in the material is already super-dispersed on the carrier.
[0175] Figure 8 The infrared spectra of the materials are shown. The uncalcined precursor ZIF-8@HCN, ZIF-67@HCN and Co / Zn-ZIF@HCN materials show the same absorption peaks, which are the same as the absorption peaks of ZIF-8 and ZIF-67, indicating that the surface of the material is coated with ZIF. The spectrum of the calcined material Figure 5 These absorption peaks disappear in b. The overall peak shapes of several materials are basically consistent with those of HCN materials. However, after careful comparison, it is found that the peak center of Zn@HCN is at 1591cm -1 The peak at 1618 cm-1 is shifted to 1618 cm-1 in materials containing Co. -1 , which may be related to the interaction between metallic cobalt and carbon and nitrogen elements in the carrier.
[0176] Fig. 9The SEM images of Co / Zn-ZIF@HCN, ZnCo@HCN and S-ZnCo@HCN materials are shown respectively. It can be found that the ZIF particles in the Co / Zn-ZIF@HCN material prepared by mixing metal zinc and cobalt are uniformly coated on the surface of the HCN material, which overcomes the problem of uneven coating of ZIF-67 alone. However, compared with the coated ZIF-8, the particle size of the surface of the composite material coated with Co / Zn-ZIF is slightly increased. Fig. 9 b is the SEM image of the ZnCo@HCN material obtained after calcination. It can be clearly observed that there is an obvious spherical structure in the ZnCo@HCN material, but there is a sticky phenomenon between the spheres. And it can be found that there are many fine particles on the spherical surface. This is because the metal organic framework coated on the surface partially reconnects the carbon and nitrogen elements after high-temperature calcination, and the originally coated ZIF shrinks at high temperature. In addition, some obvious block structures were observed in the ZnCo@HCN material, which are considered to be agglomerated metals or metal compounds. Fig. 9 In the S-ZnCo@HCN material treated with hydrochloric acid in c, this bulk structure disappears. However, the small particles on the surface of the sphere still exist, which also confirms that the small particles on the surface are not bare metal particles, but small spheres coated with carbon and nitrogen elements. These structures can be considered as many tiny reactors assembled on the hollow HCN surface, providing active sites and places for the reaction.
[0177] Fig.10 The HR-TEM images and elemental mapping images of S-ZnCo@HCN materials are shown in Figure 2. Fig.10 It can be found in (a, b) that the S-ZnCo@HCN material maintains the hollow cavity structure of the HCN material, and many small black spots evenly distributed around the HCN material are considered to be metal particles dispersed on the surface. After local magnification, it can be clearly observed that these metal particles are not directly exposed to the outside, but are wrapped by a layer of nitrogen-doped carbon. This is because the metal in the precursor material of the S-ZnCo@HCN material is confined in the metal organic framework ZIF. During the calcination process, the metal is thermally reduced to a zero-valent state to form particles, and the organic framework is carbonized to form a coating. Due to the restriction of the organic framework, the metal particles do not show obvious aggregation and growth. After measuring the lattice fringes, the fringes with a lattice spacing of 0.204nm are attributed to the 111 crystal plane of metal Co ( Fig.10 c). Fig.10 d is the polycrystalline diffraction pattern of S-ZnCo@HCN material, which is considered to expose the 001, 111 and 022 crystal planes of cobalt. No obvious lattice fringes and diffraction spots of metal Zn were found in HRTEM, which may be related to the existence form and dispersion state of metal Zn. Fig.10(ej) shows the elemental surface scanning results of S-ZnCo@HCN material. The C, N, and O elements are distributed very evenly, while the Co element appears to be aggregated into small particles, which further confirms that the metal particles in the HR-TEM image are mainly metal Co. The mapping image of metal zinc does not show an obvious hollow spherical structure. The green spots in the image occupy all the fields of view. This is because the selected zinc element in the mapping test will force points in the image, but this also shows that the content of metal zinc is very low and there is no agglomeration. Fig.10 k shows the dark field projection image of S-ZnCo@HCN material. The bright spots in the image are considered to be metal particles, which is consistent with Fig.10 The position of the metal cobalt is basically consistent, indicating that the aggregated metal particles in the figure are metal cobalt, not metal zinc or cobalt-zinc alloy. The particle size distribution diagram of the metal cobalt was obtained by measuring the particle size of the particle ( Fig.10 L)), the average particle size of metallic cobalt is 5.4 nm.
[0178] Fig.11 The valence bond structure of S-ZnCo@HCN material was studied by X-ray photoelectron spectroscopy. Fig.11 shown. Fig.11 (a) is the survey spectral data of the material. It can be found that the material contains oxygen C, N, O, Co, and Zn elements, and the mass contents of the five elements obtained through semi-quantitative analysis are 67.4%, 15.2%, 5.4%, 7.1%, and 4.9%, respectively. The nitrogen content in the material is significantly higher than that in HCN (tested in the previous chapter: 9.78%). This is because the 2-methylimidazole in the precursor material contains a large amount of nitrogen. During the calcination process, the nitrogen element was reintegrated and not all converted into gas molecules and removed. The C1s spectral data of the material was fitted into four peaks, and the peaks centered at 284.80eV, 285.98eV, 288.38eV, and 291.60eV were attributed to CC / C=C, CO / C=N, NC=N, and π-π stacking satellite peaks, respectively ( Figure 8 b). All data were corrected based on the peak position of 284.80 eV. The N1s spectrum in the material was fitted into three characteristic peaks, representing graphitic nitrogen, pyrrolic nitrogen and pyridinic nitrogen (11c). Fig.11 d is the fine energy spectrum of the 1s orbital of the O element in the material. Because the calcination was carried out in an argon atmosphere, the oxygen content in the material was low, only 5.4%. At this time, the oxygen in the material was mainly produced by organic matter and water adsorbed in the air when the material was exposed to air and stored. Through the fitting of the Zn element 2p orbital, the Zn element in the material was confirmed to be a zero-valent metal Zn ( Fig.11e). Cobalt also exists in only one valence state, but unlike the standard peak spectrum data, the binding energy of Co 2p orbital is slightly increased, and the peak centers appear at 780.1eV and 795.41eV, indicating that the cobalt in the material may exist in N-Co formation.
[0179] Table 6 is the analysis table of Zn and Co content in S-ZnCo@HCN material
[0180]
[0181] Table 6 shows the content of Zn and Co in S-ZnCo@HCN materials. The data obtained by TEM and XPS are semi-quantitative data on the surface of the materials, among which the content of metal Co is significantly higher than that obtained by ICP. This shows that the metal is still more distributed on the surface of the material. Because the element scanning in TEM is not very accurate, but the ICP test gives the quantitative content of metal Zn and cobalt, it confirms that both metal zinc and cobalt exist and are not completely lost due to acid treatment. And the content ratio of the two metals is close to the input during catalyst preparation, and the mass ratio is about 1:1.
[0182] In summary, it can be seen from Test Examples 1, 2 and 3 that the catalyst can obtain the N-alkylation product of aniline and benzaldehyde at a yield of 96% in a solvent-free KOH reaction system at 125°C for 18 hours. The reduction product of nitroaromatic compounds can also be obtained at a yield of 97% in an ethanol / water system using sodium borohydride as a hydrogen source, and the catalyst has excellent stability in both reactions and is reused 8 times with substantially unchanged reaction activity.
[0183] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a hollow nitrogen-doped carbon-supported Zn-Co catalyst, characterized in that: The following steps are involved: (1) mixing the hollow nitrogen-doped carbon-based micro-nanospheres with a polydiallyldimethylammonium chloride solution and a polydiallyldimethylammonium chloride solution respectively to obtain modified hollow nitrogen-doped carbon-based micro-nanospheres; (2) mixing the modified hollow nitrogen-doped carbon-based micro-nanospheres, zinc nitrate, cobalt nitrate, 2-methylimidazole solution and methanol to obtain hollow nitrogen-doped carbon-based nanospheres supported by a bimetallic zinc-cobalt organic framework; (3) The hollow nitrogen-doped carbon-based nanospheres supported by the bimetallic zinc-cobalt organic framework are calcined to obtain highly dispersed zinc-cobalt-supported hollow nitrogen-doped carbon-based nanosphere catalysts.
2. The method for preparing a hollow nitrogen-doped carbon-supported Zn-Co catalyst according to claim 1, characterized in that: The concentrations of the polydiallyldimethylammonium chloride solution and the polydiallyldimethylammonium chloride solution in step (1) are equal, and the concentration is 0.1 to 0.5 mol / L.
3. The method for preparing a hollow nitrogen-doped carbon-supported Zn-Co catalyst according to claim 1, characterized in that: The weight ratio of the modified hollow nitrogen-doped carbon-based micro-nanospheres, zinc nitrate, cobalt nitrate and 2-methylimidazole solution in step (2) is 2-3:0.5-1.5:0.5-1.5:
30.
4. The method for preparing a hollow nitrogen-doped carbon-supported Zn-Co catalyst according to claim 1, characterized in that: The 2-methylimidazole solution in step (2) is a 1M 2-methylimidazole methanol solution.
5. The method for preparing a hollow nitrogen-doped carbon-supported Zn-Co catalyst according to claim 1, characterized in that: The step (3) further comprises: After calcination, the calcined product was cooled to room temperature and refluxed in a 1 M hydrochloric acid solution for 3 to 6 hours.
6. The method for preparing a hollow nitrogen-doped carbon-supported Zn-Co catalyst according to claim 1, characterized in that: The calcination conditions in step (3) are: a heating rate of 3 to 6°C / min, a final temperature of 800 to 1200°C, and a constant temperature of 2 to 4 hours.
7. A hollow nitrogen-doped carbon-supported Zn-Co catalyst prepared according to the method for preparing a hollow nitrogen-doped carbon-supported Zn-Co catalyst according to any one of claims 1 to 6.
8. Use of the hollow nitrogen-doped carbon-supported Zn-Co catalyst according to claim 7 in catalyzing N-alkylation reactions and catalyzing reduction reactions of nitroaromatic compounds.
9. The use according to claim 8, characterized in that: The specific steps of using the hollow nitrogen-doped carbon-supported Zn-Co catalyst in catalyzing N-alkylation reaction are: In an inert atmosphere, aniline, benzyl alcohol, KOH and a hollow nitrogen-doped carbon-supported Zn-Co catalyst are mixed in a mass ratio of 20-40:60-80:1:5 and reacted at 100-150°C.
10. The use according to claim 8, characterized in that: The specific steps of using the hollow nitrogen-doped carbon-supported Zn-Co catalyst in catalyzing the reduction reaction of nitroaromatic compounds are: Nitrobenzene, sodium borohydride, water and hollow nitrogen-doped carbon-supported Zn-Co catalyst are mixed in a mass ratio of 200-300:100-120:200-600:1, and reacted at 25-35°C.
Citation Information
Patent Citations
Hollow carbon nanosphere based on ammonia assisted carbonization as well as preparation method and application thereof
CN108751165A
Nitrogen-doped carbon microsphere loaded with cobalt nano-particles and preparation method thereof, and applications
CN110233270A
Preparation method and application of CoS / CuS composite nitrogen-doped carbon nanomaterial
CN112142119A
Novel CO2 reduction catalyst, application and preparation method thereof
CN114797936A
Preparation method of heteroatom-doped hollow carbon material and application of heteroatom-doped hollow carbon material in lithium-sulfur battery
CN115050938A